Corrosion behaviour of lead-free and sn-pb solders in 3.5wt% NACL - Kamarul Asri, Asma (2013)
The current need to produce lead-free solders in the electronic industries makes it necessary for the replacing solders to have properties which are comparable if not better than the conventional Sn-Pb solders. Thus this research was conducted to compare the corrosion behaviour of lead-free solders with composition Sn-4.0Ag-0.5Cu (SAC405), and Sn-3.0Ag-0.5Cu (SAC305) with conventional Sn-37Pb solders. Corrosion tests were conducted using salt spray tests with 3.5% sodium chloride (NaCl) solutions. The samples were characterized after corrosion tests by using SEM, EDS and XRD. The results showed that the elements present in the solders contributed to galvanic corrosion mechanism that affected the overall corrosion behaviour of the solders.